2014
DOI: 10.1002/14651858.cd009122.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intensive glucose control versus conventional glucose control for type 1 diabetes mellitus

Abstract: Background Clinical guidelines differ regarding their recommended blood glucose targets for patients with type 1 diabetes and recent studies on patients with type 2 diabetes suggest that aiming at very low targets can increase the risk of mortality. Objectives To assess the effects of intensive versus conventional glycaemic targets in patients with type 1 diabetes in terms of long-term complications and determine whether very low, near normoglycaemic values are of additional benefit. Search methods A systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
116
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(121 citation statements)
references
References 200 publications
1
116
0
4
Order By: Relevance
“…Furthermore, the choice of regimen depended on the individual needs and circumstances of the patient, as well as the treating health professional's judgement. [8] This assertion was consistent with that of Fullerton et al [9] that there was then (in 2014) no firm evidence for specific blood glucose targets, therefore necessitating individualised therapeutic goals that take into account the patient's age, disease progression, macrovascular risk, lifestyle and disease self-management capabilities. The reviewers also concluded that patient-specific regimens to optimise glycaemic control have been made possible by the development of insulin analogues, which increase flexibility and control in the treatment of type 1 DM.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…Furthermore, the choice of regimen depended on the individual needs and circumstances of the patient, as well as the treating health professional's judgement. [8] This assertion was consistent with that of Fullerton et al [9] that there was then (in 2014) no firm evidence for specific blood glucose targets, therefore necessitating individualised therapeutic goals that take into account the patient's age, disease progression, macrovascular risk, lifestyle and disease self-management capabilities. The reviewers also concluded that patient-specific regimens to optimise glycaemic control have been made possible by the development of insulin analogues, which increase flexibility and control in the treatment of type 1 DM.…”
supporting
confidence: 56%
“…[9] These therapy-related issues [8,9] were found to be adequately addressed in the Kalafong Diabetes Clinic practice.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…These types are reviewed briefly in the coming section. [3] From 2012-2015, approximately 1.5 to 5.0 million of people died because of diabetes disease. When compared to other incurable diseases, death rate is high in the case of diabetes (i.e) nearly one person die in every 10 seconds.…”
Section: Introductionmentioning
confidence: 99%